Numerical modelling of the Angola Low and the Botswana High during a neutral and two El Ni˜no summers - Morake, Dedricks Monyai (Department of Oceanography, 2019)
The Angola Low and Botswana High pressure systems are thought to play a crucial role in the variability of summer rainfall over southern Africa. However, very little is known about their variability during the summer half of the year and how their influence on rainfall patterns during ENSO and non-ENSO summers may vary. In simple terms, a weaker Angola Low is expected to lead to decreased rainfall as is a stronger Botswana High. This study looks at the monthly evolution of the Angola Low and the Botswana High during the neutral summer of 2012/13 and the two strong El Ni˜no summers of 1997/98 and 2015/16 using the WRF model. CFSR and CFSv2 reanalyses, satellite derived winds, GPCC rainfall and TRMM satellite-derived rainfall estimates are used to validate the model. The model was integrated from September through to April for each run with observed sea surface temperature and reanalyses as boundary conditions. During the neutral summer of 2012/13, the Angola Low became clearly evident in the model during the pentad of 6-10 October whereas during the 1997/98 and 2015/16 El Ni˜no summers, it became evident during the pentads of 6-10 November and 16-20 November respectively. In addition to these differences in onset, there were also differences in the date after which the Low was no longer present in the model fields. These dates were 26-28 February 2013 and 26-31 March 1998 while in the 2015/16 case, the Low remained present throughout the whole of March. In each year, the Botswana High was present throughout the entire summer half of the year. The WRF simulation indicated that during the strong El Ni˜no event of 1997/98, the Angola Low did not weaken whereas the Botswana High was weaker than normal. However, during the strong El Ni˜no event of 2015/16, the Angola Low was weaker and the Botswana High was relatively strong. The strengthening of the Angola Low and the weakening of the Botswana High during the strong 1997/98 El Ni˜no led to substantial rainfall over southern Africa. The near to above average rainfall over subtropical southern Africa during 1997/98 was unexpected given the strength of the El Ni˜no and the SST anomalies in the Indian and Pacific Oceans. The weaker Angola Low and stronger Botswana High during the strong 2015/16 El Ni˜no led to severe drought over the region. The study highlights the importance of modulations in the Angola Low and the Botswana High for rainfall anomalies during ENSO and non-ENSO summers as very different rainfall patterns may occur over southern Africa during similar strength ENSO events. The significance of these regional circulation systems is reinforced by the fact that during the 2012/13 neutral summer, the Angola Low was stronger than average and the Botswana High was relatively weak leading to good rainfall. The relationship between the Angola Low, the Botswana High and southern Africa rainfall is found to be relatively strong through the 1979-2017 period. Thus, monitoring and better understanding these regional circulation systems is important and complements ongoing efforts to monitor and predict ENSO.